Environmental Problems In The Development Of The Master Plan Of Settlements (In The Case Of The City Of Pop, Namangan Region Of The Republic Of Uzbekistan) - Kholboev Zokirjon Khodievich (Global Scientific Publishing, 2022)
In this article, in the process of environmental assessment of urban development solutions adopted in the development of the master plan of the city of Pop, the identification of existing environmental problems in the town, the assessment of the adequacy and effectiveness of the proposed solutions and proposals to gradually achieve a favorable ecological situation in the project, and the state of the environment in the case of the implementation of the master plan prediction works are analyzed.
Keywords: ecological problem; ecological situation; environmental components; waste water problems